2021
DOI: 10.3389/fped.2021.646118
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Observation of the Correlation Between Overactive Bladder and Atopic Constitution in Children

Abstract: Objective: The present study aimed to analyze the risk factors correlated with overactive bladder (OAB), observe the effects of desloratadine in the treatment of OAB, and explore the correlation between OAB and atopic constitution in children.Methods: Correlation and binary logistic regression analysis of the medical data from 447 children clinically diagnosed with OAB from June 2019 to June 2020 were conducted. The data included a history of urticaria, eczema, itchy skin, and allergic rhinitis or allergic cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
(16 reference statements)
0
4
0
Order By: Relevance
“…There was a statistically significant increase (5.227 times) in the occurrence of OAB in asthmatic children. Zheng et al found that OAB in children was associated with atopic symptoms including eczema, skin irritation, allergic rhinitis, allergic cough, and elevated total serum IgE level [ 35 ]. Histamine activates phospholipase C via the G protein when it binds to the H1 receptor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There was a statistically significant increase (5.227 times) in the occurrence of OAB in asthmatic children. Zheng et al found that OAB in children was associated with atopic symptoms including eczema, skin irritation, allergic rhinitis, allergic cough, and elevated total serum IgE level [ 35 ]. Histamine activates phospholipase C via the G protein when it binds to the H1 receptor.…”
Section: Discussionmentioning
confidence: 99%
“…Histamine is released when mast cells are activated, resulting in inflammation and sensitivity of the bladder. Through H1 receptors, histamine can also raise the afferent nerve’s bladder sensitivity, resulting in excessive bladder contractions [ 35 37 ]. Given that atopic asthma is the most prevalent form of asthma in children, the aforementioned mechanisms can cause OAB in children with asthma.…”
Section: Discussionmentioning
confidence: 99%
“…One of our previous studies revealed that children with OAB had other common allergic symptoms, and the effective rate of treatment for OAB by avoiding allergens combined with antihistamine treatment was 96.1%, suggesting that allergic factors are involved in the pathogenesis of OAB (5). Therefore, we expanded the sample size and retrospectively analyzed the risk factors for children with OAB, evaluated the effectiveness of antihistamines in the treatment of OAB and the risk factors for ineffective treatment in patients with allergies and urodynamics in children with OAB in order to improve the understanding of the pathogenesis of OAB in children and provide new treatment ideas for children with OAB complicated with allergies.…”
Section: Introductionmentioning
confidence: 95%
“…Other symptoms involve holding manoeuvres, feeling of incomplete emptying, postmicturition dribble, and genital and lower urinary tract pain [7]. Studies were concerned with the possible association between presence of voiding dysfunction and allergic disorders [3,8].…”
Section: Introductionmentioning
confidence: 99%